Optimization of Development in Children with Special Needs through a Holistic Approach (A Study on Schools, Families, and Communities) - Kholifatul Novita Ningsih; Lintang Al-mar’atus Sholihah; Wahyu Hardiani; Hendriano Meggy (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2025)
The holistic approach aims to create a supportive environment physically, emotionally, socially, and intellectually. In schools, individualized learning strategies, curriculum adaptation, and teacher involvement are important elements. Individualized Learning Programs (PPI) are designed to meet each child's unique needs, while curriculum adaptation helps to create an inclusive learning environment. The role of the family is no less important, especially in providing emotional and psychological support and building effective communication with the school. Family involvement in children's education, such as establishing routines and providing simple directions, has been shown to increase the independence and confidence of children with special needs. In addition, the community also plays a role in creating an inclusive environment through awareness campaigns, disability-friendly facilities, and social programs. The support from this community not only helps reduce the stigma against but also improves their quality of life. This study uses qualitative methods with interview, observation, and case study techniques to explore the practice of a holistic approach to children with special needs. The results show that collaboration between schools, families, and communities is very important to optimize the development of children with special needs. This integrated approach allows to reach their maximum potential, increase independence, and contribute to society.